نظرية المضاربة في الشريعة الاسلامية وتطبيقها في البنوك الاسلامية وتنمية الاقتصاد الإسلامي في إندونيسيا (Equilibrium: Jurnal Ekonomi Syariah, 2018)
This article aims at explaining the theory of mudharabah in Islamic Sharia and its application in Islamic banking and the development of the Islamic economy in Indonesia. This study is based on field research. The method of analysis of the data used is the analysis of the content on the messages received from mudharabah in Islamic law and its application in Islamic banks and the development of the Islamic economy. The result of this research is that mudharabah is one of the most important and oldest forms of investment of funds in the Islamic Sharia. The fuqaha have agreed on the legality of mudharabah, and the evidence of legality, from the al-Qur’an, Sunnah, Ijma’, and Qiyas. The mudharabah formula in Islamic banks came as a legitimate alternative to traditional financing operations. It is one of the most important forms of Islamic finance and is thought to have been the cause of Islamic banks, which are said to be the Islamic financing formula. In Islamic banks, mudharabah is divided into absolute mudharabah and restricted mudharabah. The economic concept of mudharabah in the economic literature goes to the stock exchange and its predictions of market fluctuations. The investor may have to pay the price differentials in the case of lower prices.